Golok Cikeruh: Akulturasi Islam Mataram Eropa dan Sunda - Said, Muchamad Bachrudin; Supendi, Usman; Amir, Abdul Razak (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2024)
Cleaver is a tool to help the life of man in his day, in the law of the promotion of the culture of the law No. 5 of 2017 there are 10 objects the promotion of the culture in which there is a system of knowledge, in the system of knowledge concerning the 7 elements of culture there is a system of traditional equipment, the meaning is different with what that function Cleaver, what it the function of a hoe? What's the function of sickles? What is the function of a machete? One of them in Sundanese their Cleaver, it exists in a variety of regions, if the first in the times of the kingdom of the archipelago that has each characteristic. Cleaver Cikeruh is a weapon made in Cikeruh since the 1800s. Cleaver is manufactured in Cikeruh by a master craftsman named Raden Madjakusuma he made a Cleaver typical cikeruh which has its own uniqueness, because of cleaver result of his work can be famous even Cleaver Cikeruhan the results of his work could be known among the colonial Dutch at that time, because of its uniqueness which collaborate the shape of the shape of cleaver Europe and the shape of the Machete from Sundanese produce a unique shape and become a to unique form Cleaver Cikeruhan.Keywords: Cleaver; Local wisdom; Netherlands; Sundanese.